Analysis of Nature Ecotourism Attraction of Kedung Pedut River Flow as a Special Interest Leading in Yogyakarta - AZAHARI, Azril; ISDARMANTO, ISDARMANTO; DAMIASIH, DAMIASIH; LESTARI, Fitri Puji; SUDIRO, Syawal; NUGROHO, Dwi Yoso (Journal of Environmental Management and Tourism; Vol 12 No 5 (2021): JEMT Volume XII Issue 5(53) Fall 2021DO - 10.14505//jemt.v12.5(53).22, 2021)
This paper presents the beauty of Kedung Pedut ecotourism on its natural architectural structures. The attractiveness of creative innovation from bamboo product design that is really very specific deserves to be developed as a tourist attraction in moderate choice that is the current trend, especially for teenagers. Plenty of land for activities to do such as outbound, gathering events, fun game with natural back to nature background. The problem of managers is done independently by local people who are not professional yet. The absence of research focused on designing Kedung Pedut ecotourism development is to be more optimal from the aspect of the environment, accessibility of infrastructure and packaging of service products that can provide satisfaction for all tourists. By using qualitative research methods to get the results more real and effectively to be applied and given the variable conditions are very diverseThe results provides enlightenment to the manager of Kedung Pedut area to be more innovative, creative and professional, to understand the potential of this high natural value is not neglected. By designing strategic step how Kedung Pedut ecotourism development will become tourism icon in Kulon Progo region and the development aspect of Tourism branding of Yogyakarta Special Region (DIY) to be wider, and able to create awareness, provide excellent service and guarantee satisfaction to all tourists as well as its sustainable ecotourism development.